Multistate Survival Analysis: An Application in Breast Cancer - Kay, R. (Methods of Information in Medicine, 1984)
The extension of the proportional hazard model of Cox for survival data allows the consideration of transition times between events of interest (e.g., response, relapse, progression, etc.) and of competing risks. This paper applies these new models to a breast cancer study and gives some general remarks for the proceeding.
Keywords: Extended Proportional Hazard Model; Multistate Survival Analysis; Competing Risks; Breast Cancer